(untitled) (Research, Society and Development, 2024)
Introduction: Memory is a process in which information is encoded, stored and recalled. Although these mechanisms are widely studied, there are gaps in understanding the impact of the "Mozart Effect" on memory recall. Objective: To investigate the impact of the combination of the Mozart Effect and intestinal dysbiosis on the recall of remote fear memories in mice exposed to specific sound stimuli. Methods: Mice were randomly distributed into two groups: G1 – exposed to Mozart’s Sonata K448 during the intrauterine period and after birth; and G2 – exposed only to ambient sound. To change the composition of the intestinal microbiota, the animals were treated with antibiotics. At the same time, both groups underwent sound-shock conditioning training. They were then subjected to extinction and memory recall tests, whose behaviors were recorded on video for analysis. The comparison between both groups in the recall test was made using the Student’s t test for independent samples, considering p≤0.050 as significant. Results: There was no significant difference between the groups in the recall test (t(12)=0.799; p=0.440). The mean ± standard error of the mean was 3.04% ± 0.33% for the Mozart group, and 2.41% ± 0.81% for the Ambient group. Conclusion: Exposure to Sonata combined with intestinal dysbiosis did not significantly affect the recall of fear memories, with similar behavior between groups.